2021
DOI: 10.3390/su132212758
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Stress: Toward Sustainable Plant Strategies and Using Plant Growth-Promoting Rhizobacteria Encapsulation for Reducing It

Abstract: Salinity is one of the most important abiotic stresses that influences plant growth and productivity worldwide. Salinity affects plant growth by ionic toxicity, osmotic stress, hormonal imbalance, nutrient mobilization reduction, and reactive oxygen species (ROS). To survive in saline soils, plants have developed various physiological and biochemical strategies such as ion exchange, activation of antioxidant enzymes, and hormonal stimulation. In addition to plant adaption mechanisms, plant growth-promoting rhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 121 publications
0
22
1
2
Order By: Relevance
“…In this regard, it has been suggested that using plant growth-promoting bacteria (PGPB) may boost plants' resistance to salt stress while being eco-friendly and cost-effective (13). Especially, PGPR can improve plant salt tolerance through ion homeostasis, antioxidant generation, ACC deaminase, phytohormones, extracellular polymeric substance (EPS), volatile organic compounds, accumulation of osmolytes, activation of plant antioxidant enzymes and improved nutritional uptake (14). Some PGPR have the ability to generate cytokines, accumulate ABA and generate antioxidants that can detoxify ROS (15).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it has been suggested that using plant growth-promoting bacteria (PGPB) may boost plants' resistance to salt stress while being eco-friendly and cost-effective (13). Especially, PGPR can improve plant salt tolerance through ion homeostasis, antioxidant generation, ACC deaminase, phytohormones, extracellular polymeric substance (EPS), volatile organic compounds, accumulation of osmolytes, activation of plant antioxidant enzymes and improved nutritional uptake (14). Some PGPR have the ability to generate cytokines, accumulate ABA and generate antioxidants that can detoxify ROS (15).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive salinity can have various adverse effects on plant, including ion toxicity, osmotic stress caused by Na + and Cl − , accumulating, and oxidative stress due to the over-production of reactive oxygen species (Lu et al, 2017;Causin et al, 2020;Saberi Riseh et al, 2021). Salinity causes intracellular ion imbalance and decreases K + , Ca 2+ , and Mg 2+ concentrations in plant (Nieves-Cordones et al, 2016;Assaha et al, 2017;Manishankar et al, 2018;Isayenkov and Maathuis, 2019;Arif et al, 2020;Shahzad et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…20 Different polymers, such as gelatine, alginate, gum arabic, whey protein, xanthan, chitosan, gellan gum, starch, etc., are utilized for encapsulation. 21 Nanopesticides possess numerous advantages in comparison to conventional pesticides, like enhanced efficacy, durability, and improved potency of active components. 22 The ideal nano-biopesticides exhibit inherent properties like increased solubility and targetoriented slow release of poorly soluble active ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Encapsulation offers benefits, such as a slow and steady release of phytocomponents and preservation of encapsulated compounds against climatic conditions . Different polymers, such as gelatine, alginate, gum arabic, whey protein, xanthan, chitosan, gellan gum, starch, etc., are utilized for encapsulation . Nanopesticides possess numerous advantages in comparison to conventional pesticides, like enhanced efficacy, durability, and improved potency of active components .…”
Section: Introductionmentioning
confidence: 99%